Influence of heat generation/absorption on mixed convection flow behaviour in the presence of Lorentz forces in a vertical micro circular duct having time periodic boundary conditions: steady periodic regime - Aina, Babatunde; Isa, Sani (Zielona Góra: Uniwersytet Zielonogórski)
The problem of mixed convection flow of a heat generating/absorbing fluid in the presence existence of Lorentz forces in a vertical micro circular subjected to a periodic sinusoidal temperature change at the surface has been studied taking the first-order slip and jump effects into consideration. The research analysis is carried out by considering a fully developed parallel flow and steady periodic regime.
Keywords: mixed convection; micro circular duct; Lorentz forces; heat generation; heat absorption; slip and jump; time-periodic